Kendala Penggunaan Teknologi Informasi dalam Proses Pengembangan Materi Pembelajaran PAI di Madrasah Tsanawiyah - Sunarya, Ujang (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
The use of information technology in Islamic religious education (PAI) holds significant potential to enhance the quality of learning, yet it continues to face various challenges in Islamic schools, including at MTs Al-Inayah, Bandung City. This study aims to identify and analyze the barriers to integrating information technology into the development of PAI learning materials. The research employs a qualitative method with a literature review design, involving an in-depth evaluation of technological infrastructure, teacher competency, financial resources, and the availability of digital materials. The key findings indicate that limitations in infrastructure, lack of teacher training, budget constraints, and the scarcity of digital resources are significant obstacles hindering the integration of technology in PAI learning. The implications of this study provide crucial insights for developing more effective strategies to support the adoption of information technology in Islamic schools. Furthermore, the results contribute to the educational literature by reinforcing the understanding of local challenges faced within the context of religious education in Indonesia. This research also proposes the need for a collaborative approach among the government, educational institutions, and communities to overcome these barriers, ultimately enhancing the quality of PAI learning significantly.